2018
DOI: 10.17245/jdapm.2018.18.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of oral midazolam and triazolam premedication before general anesthesia in patients with disabilities with difficulty in cooperation

Abstract: BackgroundWhen performing dental treatment under general anesthesia in adult patients who have difficulty cooperating due to intellectual disabilities, anesthesia induction may be difficult as well. In particular, patients who refuse to come into the dental office or sit in the dental chair may have to be forced to do so. However, for adult patients with a large physique, physical restraint may be difficult, while oral sedatives as premedication may be helpful. Here, a retrospective analysis was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A study on the effectiveness of different administrative routes of midazolam suggests that oral midazolam is more commonly recommended than intramuscular injection for patients with intellectual disability [ 23 ]. Furthermore, a study comparing the patients changing cooperative levels after receiving two different types of oral premedication, midazolam, and triazolam, concluded that the effects of the two drugs were not significantly different [ 24 ].…”
Section: Considerations Of General Anesthesia For Disabilitiesmentioning
confidence: 99%
“…A study on the effectiveness of different administrative routes of midazolam suggests that oral midazolam is more commonly recommended than intramuscular injection for patients with intellectual disability [ 23 ]. Furthermore, a study comparing the patients changing cooperative levels after receiving two different types of oral premedication, midazolam, and triazolam, concluded that the effects of the two drugs were not significantly different [ 24 ].…”
Section: Considerations Of General Anesthesia For Disabilitiesmentioning
confidence: 99%
“…Since the evaluation of the Mallampati score depends on verbal commands, the amount of mouth opening and movement of the neck could not be confirmed; airway evaluation was conducted by carefully observation of the patient's movements. No abnormalities were observed but a difficult airway was expected considering the thyromental distance between the lower jaw and thyroid gland and protrusion of the anterior teeth [7].…”
Section: Discussionmentioning
confidence: 97%
“…The hypnotic agents produce somnolence and facilitate the onset and maintenance of a state of natural sleep in its electroencephalographic parameters from which the patient can be easily awakened and respond appropriately to physical stimulation and verbal command . Oral midazolam, a benzodiazepine, has been used successfully in accident and emergency medicine since 1992, and there are numerous studies on its use as premedication . Indications for conscious sedation include moderate mental and psychological disorders, such as DS, and it is often indicated for children undergoing dental treatment …”
Section: Discussionmentioning
confidence: 99%
“…It is for all these reasons that it is necessary to implement strategies for the dental treatment of patients with intellectual disabilities. The most frequent is the use of general anesthesia with or without the use of midazolam as a premedication to reduce the traumatic experience . One of these strategies is conscious sedation after psychoprophylaxis sessions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation